2021
DOI: 10.1073/pnas.2108325118
|View full text |Cite
|
Sign up to set email alerts
|

In situ investigation of water on MXene interfaces

Abstract: A continuum of water populations can exist in nanoscale layered materials, which impacts transport phenomena relevant for separation, adsorption, and charge storage processes. Quantification and direct interrogation of water structure and organization are important in order to design materials with molecular-level control for emerging energy and water applications. Through combining molecular simulations with ambient-pressure X-ray photoelectron spectroscopy, X-ray diffraction, and diffuse reflectance infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…We particularly note that H 2 S and H 2 O bind very strongly to mixed surfaces (much stronger than to the pure O-terminated surface) because the S atom of H 2 S and O atom of H 2 O can bind to the OH group and the H atoms to O groups. In fact, this result is fully consistent with reports of interlayer and surface water in MXenes (as observed, e.g., in TGA experiments), arising from its high hydrophilicity . NH 3 appears to have even stronger adsorption energy, although this situation is somewhat different.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We particularly note that H 2 S and H 2 O bind very strongly to mixed surfaces (much stronger than to the pure O-terminated surface) because the S atom of H 2 S and O atom of H 2 O can bind to the OH group and the H atoms to O groups. In fact, this result is fully consistent with reports of interlayer and surface water in MXenes (as observed, e.g., in TGA experiments), arising from its high hydrophilicity . NH 3 appears to have even stronger adsorption energy, although this situation is somewhat different.…”
Section: Resultssupporting
confidence: 92%
“…In fact, this result is fully consistent with reports of interlayer and surface water in MXenes (as observed, e.g., in TGA experiments), 54 arising from its high hydrophilicity. 55 NH 3 appears to have even stronger adsorption energy, although this situation is somewhat different. Because when NH 3 is adsorbed on the mixed surface, it captures a proton from one of the surface OHgroups (and 0.288e), resulting essentially in NH 4 + adsorbed on negatively charged MXenes.…”
Section: H 2 S Gas Sensing Mechanismmentioning
confidence: 89%
“…[ 1 ] One example of MXene, Ti 3 C 2 F x , satisfies the stoichiometric ratio of n + 1/ n , in which M, X, and T stand for transition metals, carbon or nitrogen, terminal groups at surfaces, respectively. The MXene has exhibited extraordinary electrical, [ 2–4 ] optical, [ 5 ] mechanical, [ 6–8 ] and electrochemical properties [ 9 ] since its first discovery, [ 10 ] which has become an emerging material for sensing, [ 11,12 ] communication, [ 13,14 ] energy, [ 15,16 ] environmental, [ 17 ] and healthcare applications. [ 18–20 ]…”
Section: Brief Of Mxenementioning
confidence: 99%
“…63 It has been demonstrated that Ti 3 C 2 T x can generate strong surface plasmons at energies as low as 0.30 eV. Despite extensive research into the impact of water intercalation on the structural and electrochemical characteristics of MXenes, 64 to the best of our knowledge, little is known about the optical modulations driven by water intercalation. This paper's major goal is to investigate how Ti 3 C 2 O 2 MXene's electronic and optical characteristics are affected by water intercalation.…”
Section: Introductionmentioning
confidence: 99%